RELATIVE IMPACTS OF DIFFERENT SEASONS ON THE QUALITIES ERISILK COCOONS AND ERI SILK YARN OF FOUR DIFFERENT MUTANTSTRAINS OF PhilosamiariciniBsd. - Kumar Gahlaut, Akhilesh; Arjun, Arjun (International Journal of Research -GRANTHAALAYAH, 2016)
The relative impacts of different seasons of ericulture namely May-June,July-Aug., Sep.-Oct. and Nov.-Dec on the qualities of erisilk cocoons and erisilk yarn of four different mutant strains of PhilosamiariciniViz; Yellow plain, Yellow zebra, G.B. plain and G.B. zebra have been evaluated under the reeling parameters. Results obtained indicate that the reeling performances of G.B. plain mutant strain is best in the season May-June (summer)followed by July-August (Rainy) and are relatively better in respect of qualities of eri cocoons and eri silk yarn in comparison to two other seasons namely September-October and November-December. The said variations are probably on account of the fact that May-June followed by July-August seasons provide relatively better and conducive eco-friendly environment to mutant strain than two other seasons of eri culture in respect of cocoon weight, shell weight, shell ratio, filament length of eri silk yarn, rate of eri silk tenacity of fibre and elongation percentage of fibre. The significant variations in relation to four different seasons in the qualities of eri cocoons and eri silk yarn of yellow plain mutant strain of Philosamiaricini (the popular eri silkworm among the four mutant strains) also have been found relatively better in respect of qualities of eri cocoons and eri silk yarn in all the seasons in spite of evident variation on account of genetic variabilities and differences in the genetic make-up of mutant strains.